Arah Pendidikan di Indonesia dalam Tataran Kebijakan dan Implementasi - Supardi U.S (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
There are several issues that arise related to education. Education is not the same as teaching. Education is a business that is conscious, deliberate, patterned, and can be evaluated by educators to foster and develop the potential that exists within learners. Direction of education policy at the level of the nation was held in the framework of the intellectual life of the nation that is based on faith and piety and noble character. Direction of the nation's education is aimed at producing human resources in Indonesia that have character: faithful and pious to God The Godhead, noble, healthy, knowledgeable, skilled, creative, independent, being a democratic citizen, and accountable. In the level of practice; the implementation of education has not implemented correctly in accordance with the direction of education policy. The practice at all levels; including at the level of early childhood and elementary school still more emphasis on teaching to the intellectual property in sharpening cognitive potential alone, and very little regard for moral education/character. For that, there needs to be a correction to the process of implementation of education policy to achieve quality education that produces superior human resource, righteous and noble.